FIELD SURVEY AND GEOLOGICAL EFFECTS OF THE 15 NOVEMBER 2006 KURIL TSUNAMI IN THE MIDDLE KURIL ISLANDS - Macinnes B.T.; Pinegina T.K.; Bourgeois J.; Razhigaeva N.G.; Kaistrenko V.M.; Kravchunovskaya E.A. (My University, 2009)
The near-field expression of the tsunami produced by the 15 November 2006 Kuril earthquake(Mw8.1–8.4) in the middle Kuril Islands, Russia, including runup of up to 20 m, remained unknown until weconducted a post-tsunami survey in the summer of 2007. Because the earthquake occurred between summer fieldexpeditions in 2006 and 2007, we have observations, topographic profiles, and photographs from three monthsbefore and nine months after the tsunami. We thoroughly surveyed portions of the islands of Simushir andMatua, and also did surveys on parts of Ketoi, Yankicha, Ryponkicha, and Rasshua. Tsunami runup in the near-field of the middle Kuril Islands, over a distance of about 200 km, averaged 10 m over 130 locations surveyedand was typically between 5 and 15 m. Local topography strongly affected inundation and somewhat affectedrunup. Higher runup generally occurred along steep, protruding headlands, whereas longer inundation distancesoccurred on lower, flatter coastal plains. Sediment transport was ubiquitous where sediment was available—deposit grain size was typically sand, but ranged from mud to large boulders. Wherever there were sandybeaches, a more or less continuous sand sheet was present on the coastal plain. Erosion was extensive, oftenmore extensive than deposition in both space and volume, especially in areas with runup of more than 10 m. Thetsunami eroded the beach landward, stripped vegetation, created scours and trim lines, cut through ridges, andplucked rocks out of the coastal plain.
Keywords: 37.31.19 Сейсмология; Tsunami; Kuril Islands; coastal geomorphology; tsunami deposit; tsunami erosion